Facility readiness and experience of women and health care providers in receiving and delivering obstetric care in comprehensive health posts in Ethiopia: a mixed method study - Ayehu, Temesgen; Tiruneh, Gizachew Tadele; Tesfaye, Chala (BMC Health Services Research, 2025)
Background Maternal mortality remains a critical public health issue in Ethiopia, with only half of births occurring in health facilities. To address this, the Health Extension Program (HEP) introduced comprehensive health posts (CHPs) to improve maternal and newborn health services in underserved areas. The CHPs are expected to provide essential health services to communities who live in villages that have limited access to a health center or Primary Hospital (more than one-hour walking distance). This study assessed the readiness of CHPs to deliver obstetric care and explored the experiences of women and healthcare providers. Methods A mixed-methods approach was used, combining quantitative assessments of eight CHPs using World Health Organization (WHO) service readiness tools and qualitative interviews with 22 postpartum women and 16 healthcare providers in agrarian and pastoral settings. Readiness indicators included staffing, availability of essential equipment, and service provision, while qualitative data focused on care experiences, respect, and interactions with providers. Results The CHPs had a mean readiness score of 50% for childbirth services, with agrarian settings scoring higher than pastoral ones. Staffing density averaged 4.3 health professionals per 5,000 population. While 63% of CHPs had access to water and electricity, power outages and water shortages significantly impacted service delivery. Women reported positive experiences, highlighting compassionate care and improved access due to proximity to CHPs
© The Author(s) 2025. Open Access This article is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License, which permits any non-commercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if you modified the licensed material. You do not have permission under this licence to share adapted material derived from this article or parts of it. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence,